Prenatal cannabinoid exposure and early language development - Talavera-Barber, Maria M.; Morehead, Evlyn; Ziegler, Katherine; Hockett, Christine; Elliott, Amy J. (Frontiers in Pediatrics, 2023)
The effect of prenatal cannabis exposure (PCE) on childhood neurodevelopment remains poorly understood. There is a paucity of studies describing the neurodevelopment impact of PCE in infancy. The Mullen Scale of Early Learning (MSEL) is a cognitive screening tool that can be used from birth to 68 months and includes language and motor domains. Here we aim to explore the association between PCE during pregnancy and neurodevelopmental outcomes at 12 months of age.Methods: Participants were pregnant persons/infant pairs enrolled in The Safe Passage Study, a large prospective cohort study. Inclusion criteria included data available on PCE with associated MSEL scores at 12 months of age. Exposed participants were defined as early exposure (1st trimester only) or late exposure (2nd or 3rd trimester) and were randomly matched with unexposed participants. Multiple linear regression models were performed to test associations between prenatal cannabis exposure and the five Mullen subscales: gross motor, fine motor, expressive language, receptive language, and visual reception.Results: Sixty-nine exposed and 138 randomly matched unexposed infants were included in the analyses. Mothers of children with PCE were younger with the mean age 23.7 years for early exposure (n=51) and 22.8 years for late exposure (n=18). Maternal characteristics with prenatal cannabis use include a high-school education, American Indian or Alaska Native descent, lower socioeconomic status and co-use of tobacco. There were no gestational age or sex difference among the groups. Expressive (95% CI: 2.54-12.76; p=0.0036,) and receptive language scores (95% CI: 0.39-8.72; p=0.0322) were significantly increased between late-exposed infants compared to unexposed infants following adjustment for covariates. Gross motor scores (95% CI: 1.75-13; p=0.0105) were also significantly increased for early-exposed infants with no difference in visual reception scores.Preclinical studies have shown abnormal brain connectivity in offspring exposed to cannabis affecting emotional regulation, hyperactivity, and language development. Results from this study link PCE to altered early language development within the first year of life. Exposed infants demonstrated increased expressive and receptive language scores at 12 months of age, which can translate to better performance in school. However, further research is needed to determine the implications of these results later in childhood.